Outcomes of delivery in patients with diagnosed life-limiting fetal condition and evaluation of perinatal palliative care program: a retrospective review of palliative care service over 7 years - Aleksandra Korzeniewska-Eksterowicz; Hanna Moczulska; Mariusz Grzesiak; Piotr Kaczmarek (BMC Palliative Care, 2025)
Abstract Background The parents with a diagnosis of life-limiting fetal condition should receive medical information about the nature of defect, prognosis, possibilities of care and obstetric complications and receive psychological, spiritual, legal support. In our model of care, the perinatal hospice - functioning outside the hospital structure - offers a multidisciplinary support and coordinates care in close cooperation with hospitals. The aims of study are: analysis of the birth outcome in patients with life-limiting fetal conditions, perinatal palliative care model evaluation and analysis of factors affecting earlier contact of patients with perinatal hospice. Methods We conducted retrospective reviews of medical records of perinatal hospice patients in 2014–2020. The study population was divided into two groups. Group 1 comprised deliveries which ended with the birth of a living newborn; Group 2: pregnancies with intrauterine fetal death and death during delivery. Separately, we analysed patients who underwent cesarean birth. Results Out of 72 families, 68 decided to continue pregnancy. The most common diagnoses were trisomies 18 and 13. In 47 cases, deliveries resulted in a live-born newborn; in 21 pregnancies, fetal death occurred. Nineteen pregnancies were delivered via cesarean on obstetric indications. The time interval from diagnosis to first palliative consultation was, on average, 48 days in group 1 vs. 33 in group 2. Women with stillbirths contacted the hospice at an earlier stage of pregnancy (p = 0.0469), and multidisciplinary team consultation in the hospital took place earlier (p = 0.0045) and in a shorter time interval from the first consultation in hospice (p = 0.0298). Patients who were older and lived in large cities contacted hospice earlier. Conclusion System solutions should be considered, obliging the physician to refer the pregnant woman to a perinatal palliative care program. Shortening the interval between diagnosis and palliative care consultation would allow for more effective professional support and more time to prepare the parents for losing a child.